Alternative Splicing of Differentiated Myeloid Cell Transcripts after Infection by Anaplasma phagocytophilum Impacts a Selective Group of Cellular Programs - Dumler, J. Stephen; Sinclair, Sara H.; Shetty, Amol C. (Frontiers in Cellular and Infection Microbiology, 2018)
Eukaryotic proteome diversity exceeds that encoded within individual genes, and results in part from alternative splicing events of pre-messenger RNA. The diversity of these splicing events can shape the outcome in development and differentiation of normal tissues, and is important in pathogenic circumstances such as cancer and some heritable conditions. A role for alternative splicing of eukaryotic genes in response to viral and intracellular bacterial infections has only recently been recognized, and plays an important role in providing fitness for microbial survival, while potentially enhancing pathogenicity. Anaplasma phagocytophilum survives within mammalian neutrophils by reshaping transcriptional programs that govern cellular functions. We applied next generation RNAseq to ATRA-differentiated HL-60 cells established to possess transcriptional and functional responses similar to A. phagocytophilum-infected human neutrophils. This demonstrated an increase in transcripts with infection and high proportion of alternatively spliced transcript events (ASEs) for which predicted gene ontology processes were in part distinct from those identified by evaluation of single transcripts or gene-level analyses alone. The alternative isoforms are not on average shorter, and no alternative splicing in genes encoding spliceosome components is noted. Although not evident at gene-level analyses, individual spliceosome transcripts that impact nearly all spliceosome components were significantly upregulated. How the distinct GO processes predicted by ASEs are regulated by infection and whether they are relevant to fitness or pathogenicity of A. phagocytophilum should be addressed in more detailed studies.